Proposta de método para mensuração da qualidade de políticas públicas em sistemas de inovação - Pakes, Paulo Renato (Universidade Federal de São Carlos, 2018)
Despite the development of technological capacity to innovate occur primarily within companies, other organizations and institutions of the Innovation System (IS) can contribute to this process. In the broadest sense, IS can be understood as all important economic, social, political, organizational and institutional factors, among others, that influence the development, diffusion and use of innovations. The Public Power of the State of São Paulo has carried out several initiatives in Science, Technology & Innovation for the maturation of its local innovation systems (LSI). Among the public policies implemented are the creation of the Paulista System of Technology Parks (PSTP), the Business Incubators Network (BIN), the State Innovation Law as well as the São Paulo System of Innovation Environments (SPSIE), which proposes a for the state innovation system. Considering this context, this thesis proposes a model to measure the perceived quality of public policies for Innovation System from the point of view of users. The analysis framework has as starting point the concepts of innovation and quality systems in the public sector and brings as original contribution a model to measure the perceived quality of public policies in innovation. For its accomplishment, this thesis went through the elaboration of bibliometric analysis and systematic analysis on quality in the public sector and systems of innovation. Following, a websurvey on the quality of public policy SPTec was carried out. Through descriptive analysis, it was possible to verify the quality of public policy in 5 determinants of quality. Factor analysis allowed the regrouping of quality attributes into new determinants for SPTec public policy. The Pearson correlation analysis allowed to verify the correlations between the variables. Finally, the multiple regression analysis allowed us to analyze the dependence relationship between the variables. It was observed that the public policy SPTec is immature in terms of process quality, quality of the relation and quality of the result, needing intervention of improvement with higher priority on them. In addition, we identified the determinants that should be prioritized in the implementation of SPTec public policy in a possible reformulation. Finally, the attributes of quality that generate the greatest effect in terms of increase in user satisfaction are shown, as well as those that generate decrease in satisfaction if they have an increase in their performance, which allows to analyze which attributes should be prioritized in terms of maintenance or performance. From the information obtained through the application of the instrument, public managers and public policy promoters can promote improvements in the innovation system with the aim of maturing it.
A method for measuring the quality of public policies in innovation systems
Método para mensuración de la calidad de políticas públicas en sistemas de innovación
Keywords: Políticas Públicas; Sistema de Inovação; Qualidade no setor público; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO